MAUSHUL MUSYTARAK DALAM SURAH ALI IMRAN - Fitri Ananda; Zainul Arifin; Rahmat Satria Dinata (UIN Imam Bonjol Padang, 2022)
The holy Qur'an and its meanings have uslubs that contain miracles and beautiful wording beyond the Arabic uslubs used today. To understand the holy Qur'an, it requires the mastery of Arabic sciences, especially Nahwu science, including Ism Maushul Musytarak. Therefore, the author is interested to make a research regarding to the nahwu science, especially in the title of